A Case Report on the Spontaneous Intraperitoneal Rupture of Urinary Bladder Presenting as Acute Intestinal Obstruction – Lessons Learnt - Nair, Vipin Venugopal; Sharma, Pawan; Prabhu, Swarup; Rehsi, Simarjit Singh (Lietuvos chirurgija, 2022)
Acute intestinal obstruction is a common surgical emergency. Most of the time, the cause lies in the gastrointestinal track. A 19 year old boy presented with clinical features of acute intestinal obstruction and radiological features suggestive of large bowel obstruction was taken up for surgery. During evaluation we found extravasation of urine inside pelvic cavity. Exploratory laparotomy showed intraperitoneal rent in dome of urinary bladder with dense adhesion of omentum kinking the transverse colon causing acute intestinal obstruction. We were surprised to see the resolution of obstruction with excision of omental band. The bladder was repaired and he was relieved of the problem. This article is a rare example of nongastrointestinal cause for intestinal obstruction. Most of these cases are seen by a general surgeon in an emergency setting. Hence this report is to enlighten the medical caregivers about the existence of this rare entity.